A Review on Security Constrained Economic Dispatch of Integrated Renewable Energy Systems - Tsegaye, Shewit; Shewarega, Fekadu; Bekele, Getachew (EAI Endorsed Transactions on Energy Web, 2020)
This paper presents a selective survey of papers, books, and reports that articulate recent trends of Security Constrained Economic Dispatch (SCED) of integrated renewable energy systems (IRES). The time-period under consideration is 2008 through 2020. This is done to provide an up-to-date review of the recent, major advancements in the SCED, and state-of-the-art since 2008. This helps identify further challenges needed in adopting smarter grids, and indicate ways to address these challenges. The study was conducted in three areas of interest that are relevant for articulating the recent trends of SCED. These areas are (i) SCED of power systems with IRES, (ii) SCED mathematical formulation and solution methods, and (iii) SCED challenges. The review results and research directions deduce that the state of the art research is not enough and needs special attention on following the path of artificial intelligence-based optimization.
Keywords: Security constraints; economic dispatch; economic dispatch challenges; renewable energy sources